Pattern of Presentation of Mammography in a Developing Country - Joshi, Birendra Raj (Nepalese Journal of Radiology, 2020)
Introduction: Breast cancer is the second commonest cancer (7.2%) in Nepal and almost 54% of patients present in the advanced stage. It is the leading cause of cancer death in females. The objective of the study was to determine the type of mammography, composition of breast density and BIRADS category. Methods: The study was conducted in a tertiary hospital from Jan 1st to Oct 30th of 2019 according to non-probability convenience sampling. A total of 388 persons were included in the study. The mammographic findings were assessed by categories based on the BIRADS system. Results: Mammography for screening was 38 percent and diagnostic was 68 percent. Common breast compositions were B and C. More frequent BIRADS categories were seen in 1 and 2. Conclusion: Dense breast is common in mammography. BIRADS categories 1 and 2 were more common than other categories.